An investigation of the types of reading tasks and texts in EFL textbooks and their effect on student's motivation - Stutz, Lidia (2005)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.